Chronicles of Kyphosus in the Mediterranean Sea: new records and complete mitogenomes support the scenario of one expanding fish species - Nota, Alessandro; Tiralongo, Francesco; Santovito, Alfredo; Torroni, Antonio; Olivieri, Anna (Frontiers in Marine Science, 2024)
The Mediterranean Sea is a biodiversity hotspot, being home to a vast array of marine species. Furthermore, seawater warming is facilitating the arrival and spread of new thermophilic species, posing a severe threat to biodiversity. Among the species currently extending their range and increasing in abundance in Mediterranean waters, sea chubs (genus Kyphosus) are one of the most enigmatic. One challenge arises from the high phenotypic similarity between the two congeneric species documented in the basin: Kyphosus vaigiensis and Kyphosus sectatrix. Their resemblance has often led to identification challenges, resulting in incorrect or omitted species-level classifications. Therefore, despite the growing presence of these fish in the Mediterranean, it remains unclear whether only one or both species are experiencing a demographic increase and range extension. To date, there have been 26 reports of Kyphosus individuals in the Mediterranean Sea, documented in 24 separate papers. Here, we reviewed the history of the genus in the basin and provided 13 new records of these fish from multiple localities along Mediterranean coasts. In addition, we sequenced the entire mitogenomes of two specimens, assessed their phylogenetic relationships with published Kyphosus mitochondrial DNAs from around the world, and conducted detailed morphological and meristic analyses on one of them, allowing us to provide accurate species-level identifications. Our results indicate that K. vaigiensis is the species currently expanding its range in the Mediterranean Sea, while K. sectatrix is still very rare and only sporadically reported. Notably, our mitogenome data indicate that Mediterranean K. vaigiensis individuals most likely came from Atlantic waters, while there is no evidence to support an entrance through the Red Sea or any other anthropogenic vector. Finally, the potential ecological and fishing impacts associated with the proliferation of these fish in the region are discussed.